Excessive indebtedness of LDCs? - Emil Küng (Intereconomics, 1973)
Though even in such cases there may be different opinions, it appears fairly obvious under what conditions a business is excessively indebted. However, there is hardly any agreement on the point where an entire national economy ought to be considered as overindebted. The present article discusses this problem.
Keywords: 330; Development Policy